Aumento da estabilidade térmica das matrizes cerâmicas derivadas da ortoferrita de lantânio (LaFeO3) e titanato de cálcio (CaTiO3) para operações em altas frequências (radiofrequência e micro-ondas) - Vasconcelos, Sebastião Junior Teixeira (2020)
This study describes the synthesis and characterization of novel ceramic matrix (LaFeO3)(1- m) (CaTiO3)m with many weight compositions (m) in the microwave (MW) and radio frequency (RF) regions. The materials were obtained by the solid state reaction between the oxides orthorhombic perovskites LaFeO3 (LFO) and CaTiO3 (CTO), and structurally characterized by X-ray diffraction (XRD), scanning electron microscopy/dispersive X-ray energy spectroscopy (SEM/EDS) and Mössbauer spectroscopy (MS). The analyzes indicated the formation of ceramic matrix derived from LFO with partial isomorphic occupation of the La3+ and Fe3+ sites by Ca2+ and Ti4+, respectively, with distortions on the unit cell that affected, among others, the materials density. The electrical properties in the MW region were studied for the materials in a dielectric resonant antennas (DRAs) through the parameters coefficient of resonance frequency (τf), resonance frequencies (fr), dielectric permittivity (εr) , tangent of dielectric loss (tgδ) and quality factor (Qd). For the RF region, impedance spectroscopy (IS) determined the real and imaginary parts of the impedance (Z' and Z”), the real part of the permittivity (ε’), tgδ, activation energy (Ea), conductivity (σ’), capacitance (C) and temperature capacitance coefficient (TCC). Samples with m ≤ 0.5 demonstrated to operate well in the region of the MW C band, while composition m ≥ 0.6 operate in the MW S band. Only a specific composition demonstrated high thermal stability, with τf located in the ± 10 ppmºC-1 range. The RF analyzes show colossal permittivity at 1 Hz and 30ºC for many compositions, especially m = 0.1 (ε’= 3.90 x 104 ) which is also associated with the largest tgδ in the series. LFO0.9CTO0.1 is divergent from the other samples in all RF analyzes, having the lowest Ea of the series. However, a single type of equivalent circuit are sufficient to describe the grain and grain boundary properties of all samples. For the thermal stability, the composition with m = 0.5 have the lowest variation of TCC with f. This sample has a specific frequency ranges with greater thermal stability and a possible composition between m = 0.3 and m = 0.5 with TCC = 0 at low frequencies.